Enzyme-Free Electrochemical Sensors for in situ Quantification of Reducing Sugars Based on Carboxylated Graphene–Carboxylated Multiwalled Carbon Nanotubes–Gold Nanoparticle–Modified Electrode - Liu, Ke; Wang, Xiaodong; Luo, Bin; Wang, Cheng; Hou, Peichen; Dong, Hongtu; Li, Aixue; Zhao, Chunjiang (Frontiers in Plant Science, 2022)
The in-situ detection of sugars in plants or agriculture products is very important in precision agriculture. However, the upper detection limit of the currently developed sugar sensor is not high enough for in-situ detection. In this study, an enzyme-free electrochemical sensor for in-situ detection of reducing sugars was developed. Three dimensional composite materials based on carboxylated graphene-carboxylated multi-walled carbon nanotubes attaching with gold nanoparticles (GR-MWNT-AuNPs) was formed and applied for the non-enzymatic determination of glucose, fructose, arabinose, mannose, xylose and galactose. It was demonstrated that the GR-MWNT-AuNPs modified electrode exhibited good catalysis behavior to these reducing sugars. The detection range of the sensor for glucose, fructose, arabinose, mannose, xylose, and galactose is 5-80 mM, 2-50 mM, 2-50 mM, 5-60 mM, 2-40 mM, and 5-40 mM, respectively. Compared with previous studies, the upper detection limit of our enzyme-free sugar sensor is the highest, which is more suitable for in-situ detection of sugars in agricultural products and plants. In addition, this sensor is simple and portable, with good reproducibility and accuracy, it will have broad practical application value in precision agriculture.